An experimental design of 3 kW variable speed wind turbine with doubly-fed induction generator for standalone applications - Kadiman, Sugiarto; Kartikasari, Ratna; Yuliani, Oni (Institute of Advanced Engineering and Science, 2025)
Variable speed wind turbines are suitable for isolated populations, island communities or usages in which the charge of electric lines beats the connection and upkeep charge of wind turbine. This research builds wind turbine which working over variable velocity of wind. The proposed construct incorporates three-bladed aerofoil rotor, gear box with ratio 1:8, three-phase doubly-fed induction generator, automatic voltage regulator and tower. Results verify efficacy of this installed structure at wind speed of 7.0-8.2 m/s. The proposed design generates power output at 3 kW, voltage per phase between 220 V, and frequency of 50 Hz; and exhibits noise just around 60-70 dB which is below the permissible noise threshold of 85 dB.